Mother - Wister, Owen, 1860-1938 (Salt Lake City, UT : Project Gutenberg, 1998)
"Mother" by Owen Wister is a short story written in the early 1900s and republished in 1907. A young New York couple eager to marry must wait until they can afford it. When the groom inherits money, an unscrupulous advisor leads him into risky investments that threaten their future. His fiancée offers wiser counsel, but will her advice save their fortune in time? The story illuminates the financial entanglements of America's upper classes before the 1929 crash. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Mother_(short_story)
Release date is 1998-07-01
Produced by Bill Brewer, and David Widger
Keywords: Storytelling -- Fiction; Investments -- Fiction